The winning way 2.0 : learnings from sport for managers - Bhogle, Anita; Bhogle, Harsha (New Delhi Wetland Publication, 2017)
On management mantras by way of examples from cricket and corporate world.
Keywords: Cricket -- Psychological aspects; Success in business; Teams in the workplace; Winning and losing